If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + -8n) = 93 (1 * -3 + -8n * -3) = 93 (-3 + 24n) = 93 Solving -3 + 24n = 93 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 24n = 93 + 3 Combine like terms: -3 + 3 = 0 0 + 24n = 93 + 3 24n = 93 + 3 Combine like terms: 93 + 3 = 96 24n = 96 Divide each side by '24'. n = 4 Simplifying n = 4
| 4+(5+8)=(5+8)+4 | | 4g+8=-27 | | 2w+2(a+4/1/4)=124/1/2 | | 6/r+7/r-4 | | 4(5-7m)=-92 | | x/6=43 | | -8b-(5b-2)=-89 | | 4/41x+12/41=8/41 | | 5y^2=-6y+8 | | 2-4k=54 | | -4x+5=3x-16 | | 8r+45=175.40 | | (2x+5)=log(20) | | 12=4+n/2 | | x+10=-11 | | x^3+5x+8=0 | | -x-8=6 | | -4x+5=3x+16 | | 5(1/5+c)=2/2/3 | | 2/3*5/6*14 | | 3(x+2)-4x=-2(x-3) | | 11.5=y | | 2y+3(y-2)=8y-5(y+10) | | -27+4-5= | | 56+38x= | | (x)(x+1)=156 | | 43*17= | | 5+36-13=13 | | -2-6x=52 | | 13=5+36-13 | | 2*4+6= | | 16t^2-96t-96=0 |